Analisis Pengendalian Persediaan Bahan Baku dengan Menggunakan Metode Material Requirement Planning pada Gethuk Take Tawangmangu - Eka Parya, Atiska; Widajanti, Erni (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Gethuk Take Tawangmangu is a business engaged in the production of processed foods made from cassava. One of the products it produces is gethuk, the production process requires a lot of raw materials which must be maintained so that the production process can run smoothly. Raw material inventory has a very important function and role in the company to carry out good inventory control. Without good inventory control, smooth production will be hampered, which will ultimately result in losses for the company and disappointment from customers. The aim of this research is to analyze the efficiency of cassava raw material inventory control using the Material Requirement Planning (MRP) method, which consists of the Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ) methods. The results of the research show that the total cost of raw material inventory according to the policy of the Gethuk Take Tawangmangu business owner is IDR 10,000,000 greater than the calculation using the MRP method. The total cost of raw material inventory using the Lot For Lot (LFL) method is IDR 3,600,000, EOQ is IDR 3,912,000 and using the POQ method is IDR 3,600,000. From the results of calculating the total cost of raw material inventory, the MRP method can streamline raw material inventory costs, especially the LFL and POQ methods.